Applications of demilitarized energetic materials in blasting technique - Zeman, Svatopluk; Tamchyna, Václav (Univerzita Pardubice, 2005)
The paper mentions the basic ways of disposal and/or utilization of demilitarized energetic materials (EMs). Direct application of military explosives or propellants in blasting technique is undesirable at present, primarily because of their sensitivity to outer stimuli, the markedly negative oxygen balance, and impossibility of application of mechanized charging of boreholes. One of economically effective, safe and environmentally friendly methods of utilization of these EMs lies in their application as fuel and sensitizing components of commercial explosives with approximately zero oxygen balance. It can be stated that the approach to demilitarized EMs shows how advanced a particular country is from the standpoint of both expertise and legislature.
Keywords: demilitarizace; trhaviny; speciální materiály; komerční využití